OBSERVACIONES SOBRE ENTOMOFAUNA DE SUELO Y FOLLAJE EN LA RESERVA NACIONAL RIO CLARILLO, REGION METROPOLITANA, CHILE - Solervicens, Jaime; Estrada, Patricia; Márquez, Marcela (Acta Entomológica Chilena, 2022)
The entomofauna of foliage and soil surface is studied at the Reserva Nacional Río Clarillo, Región Metropolitana de Santiago, Chile. The samples were taken during spring time in two slopes of polar and equatorial orientation respectively, in relation with the plants species that characterize each situation. A list of species collected in foliage and soil surface is provided. A great dissimilarity between the insect fauna of both ecological situations is recognized and a scarce insect-plant relationship is postulated. The temporal fluctuations of the insects communities of soil and foliage are compared; the soil surface fauna changes are probably associated with the microclimatological conditions of the soil surface, while the foliage fauna changes are related to the phenological situation of plants. Finaly, a slope effect is recognized in soil surface fauna not present in the foliage one.